Performance Evaluation of External Mixture Formation Strategy in Hydrogen-Fueled Engine - Mohammed, Kamil; M. M., Rahman; R. A., Bakar (Universiti Malaysia Pahang, 2011)
Hydrogen induction strategy in an internal combustion engine plays a vital role in increasing the power density and prohibiting combustion anomalies. This paper inspects the performance characteristics of cylinder hydrogen-fueled engine with port injection feeding strategy. To that end, a one-dimensional gas dynamic model has been built to represent the flow and heat transfer in the components of the engine. The governing equations are introduced followed by the performance parameters and model description. Air-fuel ratio was varied from a stoichiometric limit to a lean limit. The rotational speed of the engine was also changed from 1000 to 4500 RPM. The injector location was fixed in the mid-point of the intake port. The general behavior of the hydrogen engine was similar to that of a gasoline engine, apart from a reduction in the power density, which was due to a decrease in the volumetric efficiency. This emphasizes the ability of retrofitting traditional engines for hydrogen fuel with minor modifications. The decrease in the volumetric efficiency needs to be rectified.